Substantive Morphological Descriptions, Phylogenetic Analysis and Single Nucleotide Polymorphisms of Aspergillus Species From Foeniculum vulgare - Mahata, Pranab Kumar; Dass, Regina Sharmila; Pan, Archana; Muthusamy, Babylakshmi (Frontiers in Microbiology, 2022)
Ascomycetous fungi are found associated with a wide variety of substrates which range from fresh water to marine ecosystems, tropical to temperate forest soils and deserts, throughout the world over. These demystifying fungi exist as endophytes, pathogens and saprobes. They have been studied due to their ability to contaminate foods and feedstuffs, causing an elaboration of mycotoxins. Extensive analyses of the morphological features especially Aspergilli have been presented while studying them on specific mycological media. The present work is an elaborate compilation of substantive macro-morphological and micro-morphological characterization of different Aspergilli isolated from the spice Foeniculum vulgare used in India and other countries in the world. A first of its kind attempt has been made to study their molecular phylogeny and genetic relatedness to characterize the Aspergilli into specific sections, groups and clades. A total number of 27 isolates have been deposited at the National Centre for Biotechnology Information (NCBI) and five Aspergillus species have been identified and are being reported for the first time from the fennel seeds, based on partial sequence analysis of the Internal Transcribed Spacer (ITS) and beta-tubulin gene loci, coupled with phenotypic characterization. The taxonomy and current placements have been reappraised with suggestions and prospects for future research from six sections namely Terrei, Flavi, Fumigati, Nidulantes, Nigri and Versicolores. Single Nucleotide Polymorphism (SNP) analysis was carried out to evaluate the functional consequences of nucleotide variations, synonymous and non-synonymous mutations in the protein structure. The polyphasic approach of morphological identification and genetic characterization of Aspergilli from Foeniculum vulgare is presented here in adequate detail.